Computational evaluation of bioactive compounds from Vitis vinifera as a novel β-catenin inhibitor for cancer treatment - Adebesin, Ayomide Oluwadarasimi (2023)
This study features a computational approach to screen phytochemicals of V. vinifera against β-catenin, a therapeutic target protein that takes part in carcinogenesis through the wnt pathway by employing molecular docking, pharmacokinetics screening, MM/GBSA, and pharmacophore modeling approach.